The elusive measurement of symbolic effects on citizens’ political attitudes: survey experiments as alternative avenues - Espírito-Santo, A.; Verge, T. (Politics, Groups, and Identities, 2017)
In examining what the presence of female politicians symbolize to citizens, especially to women, scholars have sought to empirically prove whether it enhances the legitimacy of, closeness to, and satisfaction with political institutions, as well as levels of political efficacy and participation. By taking stock of the burgeoning quantitative research examining the symbolic effects of women’s descriptive representation on citizens’ political attitudes and behavior, we will discuss the main empirical and methodological challenges that may have led scholars to reach at best mixed results, to identify merely modest effects or to not find any trace of them. These challenges include difficulties in properly establishing the causal effects and in operationalizing the dependent variable as well as a dearth of adequate data. Our contribution discusses the advantages provided by new methodological avenues, such as survey experiments vis-à-vis standard public opinion surveys, to circumvent the shortcomings identified.